UTILIZATION OF NON-TIMBER FOREST PRODUCTS (PINE RESIN AND RESIN) FOR COMMUNITY EMPOWERMENT - Agung Sofyan; Rita Retnowati; Yossa Istiadi (Journal of Science Innovare, 2021)
Management of forest areas will not be separated from the involvement of the surrounding community. land rights and natural resources, including forests, can be managed communally so that the benefits are shared by the whole community as well as individually to meet the needs of each family. One form of forest management that involves the community is the utilization of non-timber forest products by the community around the forest. The purpose of this study is to analyze and describe the achievement or success of using non-timber forest products (pine resin and resin) after the issuance of the Minister of Environment and Forestry Regulation Number P.43/Menlhk/Setjen/Kum.1/6/2017 and the Director's Regulation. General of the Directorate General of Conservation of Natural Resources Ecosystems Number P.6/KSDAE/Set/Kum.1/6/2018 in increasing awareness and participation of non-timber forest product users in conservation activities of the Mount Halimun Salak National Park Area. This study uses the CIPP (Context – input – process – product) method, which is an evaluation model on the Context, Input, Process and Product aspects. Data obtained from the results of document analysis, field observations and interviews. Based on the data analysis, it can be concluded that the use of non-timber forest products (Sap Pinus and Damar) for community empowerment in Mount Halimun Salak National Park is feasible to be applied as an effort to improve the living standards of communities around the area while maintaining the sustainability of Mount Halimun Salak National Park. The context aspect is categorized as good and can be the main basis for implementing the program, the input aspect is categorized as sufficient, it is necessary to increase the capacity of human resources (accompaniment officers and community groups), especially in terms of institutional strengthening and group economic business development as well as business development training and training in the field of Natural Resources Conservation. Ecosystem, the Process aspect is categorized as sufficient, it is necessary to consider the existence of coaching, mentoring, monitoring and evaluation activities involving the parties (village government, related agencies from the local Government and/or Non-Governmental Organizations), and the Product aspect is categorized as good, it is necessary to continue to improve assistance and fostering so that group independence continues to increase, both institutionally, economically, as well as awareness to participate in maintaining the sustainability of the Mount Halimun Salak National Park area.